The Understanding by Design Strategy in 21st-Century Education - Dari, Wulan; Hidayat, Saleh; Wulandari, Eka (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The 21st-century learning One, solution that can be used is by using the Understanding by Design (UbD) curriculum. The aim of this research is to examine the application of UbD in teaching, the implementation of UbD in Indonesia, expected student learning outcomes within the UbD framework, and the role of teachers in the implementation of UbD. The method used is the literature study method. The data analysis technique uses deductive qualitative analysis. The results obtained are that UbD learning can be used as a reference in preparing learning implementation plans that are oriented towards learning goals. Learning using UbD has not been fully implemented by all teachers in Indonesia, because there are still many teachers who prioritize the results of final grades rather than students' understanding. The implementation of UbD has actually been planned in the latest curriculum, namely the independent curriculum, but this curriculum has not been fully implemented by all schools. In implementing UbD, students are expected to have 6 abilities, namely explaining, interpreting, applying, taking a perspective, empathizing and having self-knowledge. The role of teachers is very essential in UbD, which involves designing, implementing, and directing learning activities.ABSTRAK. Pembelajaran abad 21, salah satu solusi yang dapat digunakan yaitu dengan menggunakan kurikulum Understanding by design (UbD). Tujuan penelitian ini yaitu untuk mengkaji penerapan UbD dalam pembelajaran, implementasi UbD di Indonesia, hasil pembelajaran peserta didik yang diharapkan dalam kerangka UbD dan peran guru dalam implementasi UbD. Metode yang digunakan yaitu dengan metode studi kepustakaan. Teknik analisis data menggunakan analisa kualitatif deduktif. Hasil yang didapatkan yaitu strategi UbD dapat dijadikan sebagai acuan dalam menyusun perencanaan pelaksanaan pembelajaran yang berorientasi kepada tujuan pembelajaran. Pembelajaran menggunakan UbD belum sepenuhnya diterapkan oleh semua guru di Indonesia, karena masih banyak guru yang mementingkan hasil nilai akhir dibandingkan pemahaman peserta didik. Penerapan strategi UbD sebenarnya sudah dicanangkan di kurikulum terbaru yaitu kurikulum merdeka, tetapi kurikulum ini belum sepenuhnya diterapkan oleh semua sekolah. Pada penerapan strategi UbD, peserta didik diharapkan memiliki 6 kemampuan yakni menjelaskan, interpretasi, menerapkan, melakukan perspektif, berempati dan memiliki pengetahuan diri. Peran guru sangat esensial dalam UbD, yaitu merancang, melaksanakan dan mengarahkan kegiatan pembelajaran.